The 'Kilnsea-boat', and some implications from the discovery of England's oldest plank boat remains
A single plank with integral cleats, recently discovered on the East Riding of Yorkshire coast at Kilnsea, has been identified as a fragment of a Bronze Age plank boat, and dated to 1870Ð1670 BC. This makes the 'Kilnsea-boat' England's oldest dated plank built boat.